Discourse of Rural Development in Indonesia Local Media - Ika Yuliasari; Amiruddin Saleh; Musa Hubeis; Sarwititi Sarwoprasodjo (Institut Pertanian Bogor, 2014)
AbstractThis article describes the existence of local media, discourse of media information dissemination, and implication of construction of reality in local media. Furthermore, this article contributes in study about top down communication and bottom up communication in rural development, especially in Yogyakarta, Indonesia. The change of development paradigm in the world has involved the communication development shift after 1970. The old model of communication development have been rising since the implementation of modernization in the third world. With the pattern of trickle down effect, communication model have been designed as the linier communication process. Nowadays, we can learn about the phenomenon: development communication in globalization, human interaction as information society, roles of ICT (Information and Communication Technology), participation of grass root in community development, and more. Because of that reasons the application of linier communication model does not suitable for the communication system in rural development. Therefore the development communication have no relevance with another system in globalization era. Indonesia is a developing countries with many issues of rural development such as the poverty, political intrigue, conflict of interest, disparity of wealthiness, and sovereignity. Huge amount of the rural community in Indonesia should be the consideration in development policies. Local society in Yogyakarta have strong cultural heritage. Information flow in communication development will be an important point of the communication effectiveness. The grass root people in local area need the right informations which are related with the struggle to reach sovereignity. According to the social culture factor, many local media and community media did the construction of media news with local wisdom discourse.Key words: development, development communication, local media, community media, construction of reality, local wisdom.